Enhancing Gastrointestinal Disease Diagnosis with KNN: A Study on WCE Image Classification - Randi Rizal (International Journal of Artificial Intelligence in Medical Issues, 2023)
This study explores the application of the K-Nearest Neighbors (KNN) algorithm, following Sobel segmentation and Hu Moment feature extraction, to classify Wireless Capsule Endoscopy (WCE) images into Normal and Ulcerative Colitis conditions. Through a rigorous 5-fold cross-validation approach, the research aimed to determine the KNN algorithm's accuracy, precision, recall, and F1-score on the WCE Curated Colon Disease Dataset. The findings revealed high performance across all metrics, with accuracy rates extending up to 90.625%. The confusion matrix provided further validation, illustrating a high true positive rate coupled with a low false negative rate. These results substantiate the hypothesis that employing edge detection and shape descriptors as pre-processing techniques can significantly enhance the efficacy of machine learning algorithms in medical image classification. The study’s contribution is twofold: it reaffirms the potential of machine learning in the advancement of medical diagnostics and provides a methodological framework for automated image classification that can assist clinicians. It is recommended that future research extends to broader datasets and explores various algorithms to enhance diagnostic precision. In practice, integrating this research into a clinical decision support system could revolutionize diagnostic processes, offering a non-invasive, accurate, and efficient tool for gastroenterological diagnostics.